Encorafenib Acts as a Dual-Activity Chemosensitizer through Its Inhibitory Effect on ABCC1 Transporter In Vitro and Ex Vivo - Yu Zhang; Dimitrios Vagiannis; Youssif Budagaga; Ziba Sabet; Ivo Hanke; Tomáš Rozkoš; Jakub Hofman (MDPI AG, 2022)
Encorafenib (LGX818, trade name Braftovi), a novel BRAF inhibitor, has been approved for the treatment of melanoma and colorectal cancer. In the present work, we evaluated encorafenib's possible antagonistic effects on the pharmacokinetic mechanisms of multidrug resistance (MDR), as well as its perpetrator role in drug interactions. Firstly, encorafenib potently inhibited the efflux function of the ABCC1 transporter in drug accumulation assays, while moderate and null interaction levels were recorded for ABCB1 and ABCG2, respectively. In contrast, the mRNA expression levels of all the tested transporters were not altered by encorafenib. In the drug combination studies, we found that daunorubicin and topotecan resistances were synergistically attenuated by the encorafenib-mediated interaction in A431-ABCC1 cells. Notably, further experiments in ex vivo patient-derived explants confirmed the MDR-modulating ability of encorafenib. Advantageously, the overexpression of tested drug efflux transporters failed to hinder the antiproliferative activity of encorafenib. In addition, no significant modulation of the CYP3A4 enzyme's activity by encorafenib was observed. In conclusion, our work indicated that encorafenib can act as an effective chemosensitizer targeting the ABCC1-induced MDR. Our in vitro and ex vivo data might provide valuable information for designing the novel effective scheme applicable in the clinical pharmacotherapy of BRAF-mutated/ABCC1-expressing tumors.